INTEGRATING ZAKAT CAPITAL ASSISTANCE WITH SOCIAL ENTREPRENEURSHIP: A SUSTAINABLE MODEL FOR EMPOWERING ASNAF MICROENTREPRENEURS IN MALAYSIA - Abdullah, Shuhairimi; Ishak, Aida Shakila; Daud Fhiri, Nur Suriaty; Hussin, Noor Salwani; Azmin, Adi Anuar; Tengku Yaakob, Tengku Kastriafuddin Shah; Ramli, Abdul Jalil (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study proposes an innovative Zakat Social Enterprise Model (ZSEM) that integrates Islamic social finance with social entrepreneurship principles to empower Asnaf microentrepreneurs in Malaysia, with particular focus on rural women in Perlis. Through qualitative interviews with 12 Asnaf beneficiaries and participatory focus group discussions, we identify critical intersectional barriers including gender disparities, geographic isolation, and financial exclusion that hinder effective utilization of Zakat capital. The research adopts a community-based approach to co-develop sustainable solutions tailored to rural contexts, such as mobile banking access, childcare- inclusive business models, and halal market linkages. Our findings demonstrate that combining Zakat funds with structured entrepreneurial support can significantly enhance business viability, with pilot data showing 60% higher survival rates compared to conventional aid models. The proposed ZSEM framework operationalizes Maqasid al-Shariah by incorporating Shariah-compliant financing (Qard al-Hasan), digital financial literacy training, and gender-responsive policy measures, ensuring alignment with Islamic economic principles and Sustainable Development Goals (SDGs 1, 5, 8). Key policy recommendations include blockchain-based Zakat transparency systems and a National Zakat Entrepreneurship Taskforce to institutionalize best practices. This study contributes to Islamic social finance and inclusive development literature by providing an actionable model for transitioning Asnaf communities from aid dependency to economic self-sufficiency.